Engineering for Rural Development 2019
DOI: 10.22616/erdev2019.18.n263
|View full text |Cite
|
Sign up to set email alerts
|

Impact of compost application in vineyards on changes of physical properties of soil

Abstract: Organic matter is one of the key factors with a direct impact on the soil fertility. The lack of availability of organic matter and its lack in the soil represent a current pan-European problem. Organic matter in soil plays an unmistakable role in formation of soil and improvement of the physical properties, such as soil water retention, bulk density, soil aggregation capacity, water and air mode of soil, etc. This article discusses the evaluation of influence of compost and compost with Lignohumax applied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Different results have been obtained in previous studies regarding the effect of compost and other organic materials on the growth, yield and quality of grapevine (Pinamonti, 1998;Morlat, 2008;Mugnai et al, 2012;Tardaguila et al, 2018;Burg et al, 2019). Overall, the effects of compost on yield were found to be minor in some studies.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Different results have been obtained in previous studies regarding the effect of compost and other organic materials on the growth, yield and quality of grapevine (Pinamonti, 1998;Morlat, 2008;Mugnai et al, 2012;Tardaguila et al, 2018;Burg et al, 2019). Overall, the effects of compost on yield were found to be minor in some studies.…”
Section: Discussionmentioning
confidence: 74%
“…Although Burg et al (2019) stated that applications of organic matter improve soil fertility and physical properties (such as soil water retention, soil aggregation, water and aeration of soil, etc.) the effects of applications on yield and quality components (including soil moisture and temperature) was not seen in their two-year study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blending compost with biochar (charged biochar) during the process or after the process 4 of composting, reduces subsequent C and N losses (Meyer-Kohlstock et al 2015;Meyer et al 2014), and enhances C sequestration (Niehues 2015). Application B+Com in vineyards was found to increase soil organic C, supply nutrients, enhance soil biological activities with no adverse effect on crop yield or fruit quality (Burg et al 2019;Bustamante et al 2010;Döring et al 2019;Safaei Khorram et al 2019). Sánchez-Monedero et al (2019) found that B+Com increased grape yield, fruit quality and titratable acidity, but reduced total soluble solids content in Friuli Venezia Giulia, Italy.…”
Section: Introductionmentioning
confidence: 98%